Survival of severely compromised endodontically treated teeth restored with or without a fiber glass pos - Ribeiro, Maria Tereza Hordones; Oliveira, Gabriella de; Oliveira, Helena Letícia Quirino de; Mendoza, Lilibeth Carola Leyton; Melo, Calebe de; Peres, Thiago Silva; Soares, Carlos José (Journal of Applied Oral Science, 2023)
Objective: The use of a fiber glass post (FGP) type and choice of FGP diameter to restore endodontically treated incisors without ferrule is controversial. This study evaluated survival rate and failure mode of severely compromised central incisors without ferrule rehabilitated using resin-based composite (RBC) with or without FGP with different diameters. Methodology: A total of 60 decoronated bovine incisors without a ferrule were endodontically treated and prepared for 1.4, 1.6, and 1.8 mm diameter FGPs (Whitepost System DC 0.5, Fit 0.4, and DCE 0.5; FGM). Half of the teeth received FGPs cemented using dual-cure resin cement (Allcem Core; FGM), the other half were filled using only bulk-fill RBC (OPUS Bulk Fill; FGM). The crowns were directly restored with RBC. The roots were embedded in polystyrene resin and the periodontal ligament was simulated with polyether impression material. Fatigue testing was conducted under 5 Hz cyclic loading at 30 degrees to the incisal edge, beginning at 50 N (5,000 cycles) as a warmup. After, the load was increased 100 N every 15,000 cycles until fracture occurred. All specimens were subjected to transillumination, micro-CT analysis, and digital radiography before and after fatigue testing. Fracture mode was classified according to severity and repair potential. Data were analyzed with Kaplan-Meier survival test and post hoc log-rank test (α=0.05) for pairwise comparisons. Results: Using FGP significantly increased the number of cycles to failure, irrespective of FGP diameters (p=0.001). The FGP diameters had no statistically significant effect on cycles to failure or failure mode. Conclusion: Using FGP without ferrule improved survival rate of structurally severely compromised central incisors compared with rehabilitation without FGP. The diameter of the FGPs had no effect on the survival rate and failure mode.